The control of respiratory diseases in medical students - Pastor Balcazar, Mario (1956)
Between the control of respiratory diseases in medical students, the TB is the paramount. The Chair of Tuberculosis and Respiratory Diseases considers the problem of tuberculosis in medical students is one of the most important and unique horn integral part of national tuberculosis control and requires special attention to ensure that the student sector is present lowest possible rates of morbidity and mortality from tuberculosis.